Assessing the Agreement Between Diffusion Tension Imaging (DTI) and T2-Weighted MRI Sequence for Biometry of the Fetal Corpus Callosum - Liel N. Cohn; Shai Bookstein; Tamar Laytman Klein; Nadia Mordenfeld Kozlovsky; Tomer Ziv-Baran; Arnaldo Mayer; Eldad Katorza (Diagnostics)
Background/Objectives: Little is known about the advantages of Diffusion Tensor Imaging (DTI) when evaluating the fetal corpus callosum (CC), a sensitive indicator for normal brain development. This study evaluates the contribution of DTI compared to T2-weighted imaging to assess fetal CC biometry. Methods: Data from the fetal MRI exams of singleton pregnancies between July 2017 and 2019 were retrospectively analyzed. Mid-sagittal sections were used to measure the CC biometry, and inter- and intra-observer agreements were assessed using the interclass correlation coefficient (ICC), targeting an ICC above 0.85. Results: The results from 100 patients (mean gestational age, 32.24 weeks) indicated excellent inter-observer reliability for DTI (ICC = 0.904, 95% CI = 0.815–0.952) and moderate agreement for T2-weighted imaging (ICC = 0.719, 95% CI = 0.556–0.842). Intra-observer assessments showed excellent reliability for both DTI and T2-weighted imaging (ICC = 0.967, 95% CI = 0.933–0.984 and ICC = 0.942, 95% CI = 0.884–0.971, respectively). However, a comparison between DTI and T2-weighted images for CC biometry showed poor agreement (ICC = 0.290, 95% CI = 0.071–0.476). Conclusions: In conclusion, the study highlights a lack of agreement between DTI and T2-weighted imaging in fetal CC biometry, suggesting the need for further research to understand this discrepancy and the role of DTI in fetal health.